Host plant-mealybug (Phenacoccus solenopsis) interaction: A review - Shahid, Muhammad Rafiq; Ilahi, Farrukh; Tatheer e Zahra; Saeed Ur Rehman, Hafiz; Qureshi, Muhammad Mubashir; Kanwal, Sadia; Anjum, Naveeda; Abbasi, Khalida Hamid; Feroze, Muhammad Aqeel (Journal of Pure and Applied Agriculture, 2023)
One of the most significant insect pests of cotton is the cotton mealybug, technically known as Phenacoccus solenopsis. Up to 14% of Pakistan's economy was thought to have suffered in 2005 as a result of cotton mealybug. It is now believed to be widespread around the globe, although during the months of September and October when temperatures are mild, its population increases. It feeds in a polyphagous manner. The environmental factors and CMB's predilection for particular host plant species determine its biological properties. Under conditions of severe CMB infestation, the attacked plants show signs of leaf defoliation and seem to have been sprayed with a defoliant. The majority of farmers now use pesticides to maintain their crops. Integrated Pest Management is the most suitable option and host plant resistance is the basic component for the management of insect pests. It is a safe way to manage mealybug without the harmful effect of pesticides on the environment and non-targeted beneficial fauna. Plants protect themselves from insect pest herbivory due to host plant resistance mechanisms. This invasive species has the ability to grow farther and can increase its host range due to the variety of hosts it can find under various climatic conditions. In this work, the relationship between plants and mealybugs has been described in detail.